Carbohydrates for improving the cognitive performance of independent-living older adults with normal cognition or mild cognitive impairment. - Cheow, Peng Ooi; Yassin, Zaitun; Tengku Abdul Hamid, Tengku Aizan; Seng, Cheong Loke (EBSCO Publishing, 2008)
Mild cognitive impairment (MCI) is an intermediate state between normal cognition and dementia in which daily function is largely intact. This condition may present an opportunity for research into the prevention of dementia. Carbohydrate is an essential and easily accessible macronutrient which influences cognitive performance. A better understanding of carbohydrate-driven cognitive changes in normal cognition and mild cognitive impairment may suggest ways to prevent or reduce cognitive decline.